Morfometria dos compartimentos hidrológicos do município de Jaboticabal, SP - Arraes, Christiano Luna; Pissarra, Teresa Cristina Tarlé [UNESP]; Rodrigues, Flávia Mazzer [UNESP]; Zanata, Marcelo [UNESP]; Campos, Sérgio [UNESP] (My University, 2010)
The objective was to characterize morphometric characteristics in hydrological catchments at Jaboticabal Municipality, São Paulo State, Brazil. Techniques of digital image processing and Geographic Information System (GIS) were used to collect data as size, topography and drainage pattern of the hydrological areas. Drainage density was considered low, below 2 km/km²; basin density was less than 1.0 channel/km². The hydrological catchments are poorly susceptible to flooding during normal rainfall. The morphometric parameters of hydrological catchments at the Jaboticabal Municipality were used for planning and environmental management.

O objetivo do trabalho foi caracterizar morfometricamente os compartimentos hidrológicos pertencentes ao Município de Jaboticabal, Estado de São Paulo. Técnicas de processamento digital de imagens e Sistema de Informação Geográfica (SIG) foram utilizadas para a coleta de dados de dimensão, padrão de drenagem e relevo dos compartimentos hidrológicos. A densidade de drenagem foi considerada baixa, inferior a 2 km/km² e a densidade hidrográfica foi inferior a 1,0 canal/km². Os compartimentos hidrológicos mostram-se pouco suscetíveis à enchente em condições normais de precipitação. Os parâmetros morfométricos dos compartimentos hidrológicos pertencentes ao Município de Jaboticabal serviram para o planejamento e gestão ambiental.
Morphometry of the hydrological compartments in Jaboticabal municipality, SP
Keywords: Hydrographic; SIG; Areal analyses; Hidrografia; SIG; Calculo areal